Diversity, dissent, and fragmentation in the #MeToo movement: the role of collective and individual dimensions - Bliuc, Ana-Maria; Hamilton, Tayla; Muntele, Daniela (Frontiers in Psychology, 2024)
Society is often deeply divided across fault lines caused by dissent on important social issues such as global warming, immigration, gun control, and gender equality (Abramowitz & Saunders, 2008;Ramos et al., 2015). How we position ourselves in relation to such issues creates ideologically opposed campsthat is, psychological groups based on contrastive collective narratives about important aspects of social reality (Bliuc et al., 2020;2021).Ideologically opposed camps are underpinned by a group consciousness (Duncan, 2012)